Fabrication Of Porous Carbonated Hydroxyapatite By A Sponge Template And Carbonation Technique - ., Sunarso (2012)

(untitled)
Porous carbonated hydroxyapatite (C-HAP) was successfully fabricated by a sponge template and carbonation technique from micron-sized commercial HAP powders and synthesized nano-sized HAP powders. The carbonation of the porous HAP, performed during the cooling stage of the sintering process under wet carbon dioxide (CO2) gas, was successful in incorporating CO3 2- ions into porous HAP. Carbonation was carried out at three different cooling temperatures (200, 300 and 400oC) and flow times (20, 40 and 60min). The optimum condition for carbonation in terms of CO3 2- content was obtained after the gas had been passed through at a cooling temperature of 200oC for 60min. It was found that an increase in cooling temperature resulted in a decrease in CO3 2- ion content, whilst a longer flow time yielded in an increase of CO3 2- ion content. Mg(NO3)2, which was equivalent to 1, 3, 5 and 7 wt% of MgO, was added to enhance the mechanical strength of porous C-HAP. The compressive strength of porous C-HAP reached the highest value after an addition of Mg(NO3)2 equivalent to 1 wt% of MgO. It was observed that the porous C-HAP fabricated from nanoemulsion-derived HAP powders possessed a higher CO3 2- ion content (1.70 wt%) compared to that of porous C-HAP fabricated from micron-sized commercial HAP powders (1.25 wt%), indicating that the smaller particle size of the starting material might have enhanced the reactivity of the porous specimens to CO2 gas during carbonation. After immersion in SBF solution for 1, 2 and 4 weeks at 36.5±1.0oC, apatite-like layer grew faster in the porous C-HAP with higher CO3 2- ion content, suggesting that the carbonation technique used in this study was able to enhance the bioactivity performance of the porous product.